2004
DOI: 10.4141/p04-022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N and P fertilization on growth, seed yield and quality of industrial hemp in the Parkland region of Saskatchewan

Abstract: Industrial hemp (Cannabis sativa L.) has sparked renewed interest in western Canada in recent years, and there is very little research information available on its fertilizer requirements. The objective of this study was to determine the effect of surface-broadcast ammonium nitrate and seedrow placed monoammonium phosphate fertilizers on the production and seed quality attributes of industrial hemp (cv. Fasamo and Finola). Field experiments were conducted on a Black Chernozem silty loam soil at Melfort, Saskat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 16 publications
7
54
0
Order By: Relevance
“…However, highly variable biomass yields were observed for all genotypes and fertilization treatments, which ranged from 25.4 Mg ha −1 at the control in ʽBialobrzeskie᾽ to 187.7 Mg ha −1 at the highest fertilization dose in ʽFutura 75᾽ (Table 3). Increasing the rate of N fertilizer led to an increase in inflorescence length and weight (Vera et al, 2004;Campiglia et al, 2017). Nitrogen availability has little effect on hemp seed mass and in our study there were no significant Table 2.…”
Section: Resultsmentioning
confidence: 44%
See 2 more Smart Citations
“…However, highly variable biomass yields were observed for all genotypes and fertilization treatments, which ranged from 25.4 Mg ha −1 at the control in ʽBialobrzeskie᾽ to 187.7 Mg ha −1 at the highest fertilization dose in ʽFutura 75᾽ (Table 3). Increasing the rate of N fertilizer led to an increase in inflorescence length and weight (Vera et al, 2004;Campiglia et al, 2017). Nitrogen availability has little effect on hemp seed mass and in our study there were no significant Table 2.…”
Section: Resultsmentioning
confidence: 44%
“…In contrast, significant yield increases were reported in nitrogen limiting conditions (Van der Werf et al, 1995;Struik et al, 2000;Amaducci et al, 2002;Aubin et al, 2015). Vera et al (2010Vera et al ( , 2004 reported that hemp seed yield increased progressively with increasing nitrogen availability under a high fertilization rate, which ranged from 99 kg N ha −1 to 198 kg N ha −1 depending on growing conditions. According to several studies conducted in the Netherlands, England, Latvia and Italy, nitrogen fertilization rates ranged between 100 and 240 kg N ha -1…”
Section: Experimental Design and Treatmentsmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, rainfall during the duration of the study was considered adequate at all locations, which contrasted with a previous similar study (Vera et al 2004), in which drought prevented the utilization of applied fertilizer in 2 of 3 yr.…”
Section: Nitrogenphosphorus Studymentioning
confidence: 65%
“…Research from eastern Canada, between 1923and 1942(Gehl 1995, however, showed that hemp fibre cultivars did respond to additional fertilizer and manure. More recently, a preliminary fertility experiment, conducted near Melfort, Saskatchewan (Vera et al 2004), indicated that seed yield and biomass of two grain hemp cultivars were increased by 64 and 94%, respectively, when up to 120 kg N ha…”
mentioning
confidence: 99%